1997
DOI: 10.1086/133993
|View full text |Cite
|
Sign up to set email alerts
|

Optical Night-Sky Brightness at Mauna Kea over the Course of a Complete Sunspot Cycle

Abstract: ABSTRACT. We have produced a database of V band and B band night-sky brightness measurements rather evenly spread out over the course of a whole sunspot cycle from September 1985 to August 1996. Almost all the data were obtained at the 2800-m level of Mauna Kea using the same telescope, same photomultiplier tube, filters, and diaphragm, thus minimizing various sources of systematic error and allowing an estimate of the sources of random error. The yearly V band averages of observed sky brightness ranged from 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 15 publications
7
47
0
1
Order By: Relevance
“…Since the source of sky brightness is mostly within the earth's atmosphere, we removed our 0.17 mag air mass À1 extinction correction for our images around new moon and found that the average brightness of the night sky at zenith near new moon was approximately v ¼ 21:78. This is in good agreement with the measurements of Krisciunas (1997), who found a surface brightness of 21:77 AE 0:12 at approximately the same time in the solar cycle (2 yr past the solar maximum).…”
Section: Data Reductionsupporting
confidence: 92%
“…Since the source of sky brightness is mostly within the earth's atmosphere, we removed our 0.17 mag air mass À1 extinction correction for our images around new moon and found that the average brightness of the night sky at zenith near new moon was approximately v ¼ 21:78. This is in good agreement with the measurements of Krisciunas (1997), who found a surface brightness of 21:77 AE 0:12 at approximately the same time in the solar cycle (2 yr past the solar maximum).…”
Section: Data Reductionsupporting
confidence: 92%
“…Krisciunas (1997) notes that, on average, the zenith sky brightness over Mauna Kea shows a not very convincing sky brightness change of 0.03 mag hour −1 . On the other hand he also reports cases where the darkening rate was as large as 0.24 mag hour −1 and discusses the possibility of a reverse Walker effect taking place during a few hours before the beginning of morning twilight.…”
Section: Sky Brightness Variations During the Nightmentioning
confidence: 99%
“…Rayleigh (1928) and Rayleigh & Jones (1935) were the first to note a correlation between the sky brightness and the 11 year solar cycle. This is due to the airglow being brighter at solar maximum and fainter at solar minimum (Krisciunas 1997;Krisciunas et al 2007). The 10.7 cm radio flux of the Sun is widely used as an index of solar activity.…”
Section: Sources Of Sky Brightnessmentioning
confidence: 99%